Meslek yüksekokulu öğrencilerinin zaman yönetimi ve akademik başarıları arasındaki ilişki - (:unkn) unknown (My University, 2010)
Öğrencilerin özellikle yüksek öğretim aşamasında zamanlarını iyi yönetmesi, kişisel gelişim ve akademik performans başta olmak üzere pek çok açıdan önemlidir. Literatürde öğrencilerin zaman yönetimi ile ilgili çalışmalardan farklı olarak, bu çalışma, Teknik Bilimler Meslek Yüksekokulu öğrencileri ile yapılan ilk çalışmadır. Bu araştırmada; öğrencilerin zaman yönetimi becerileri ile akademik başarıları arasında bir ilişki olup olmadığı sorusuna cevap aranmıştır. Bu amaçla, öğrencilere zaman yönetimi anketi uygulanmış ve aldıkları puanlar hesaplanmıştır. Akademik başarıları, bölümlerde ortak olan Türk Dili-1 dersi ve Matematik-1 derslerinin ortalaması alınarak oluşturulmuştur. Zaman yönetimi anketinden aldıkları puan ile akademik başarı ortalamalarıı arasında bir ilişki olup olmadığı araştırılmıştır. Veri toplama aracı olarak öğrencilere anket uygulanmıştır. Zaman Yönetimi Anketi olarak adlandırılan veri toplama aracı 2008- 2009 öğretim yılı mayıs ayı içerisinde Marmara Üniversitesi Teknik Bilimler Meslek yüksekokulu öğrencilerine uygulanmıştır. Uygulanan anket iki bölümden oluşmaktadır. ZYA’nın birinci bölümünde öğrencilerin demografik özelliklerini ve akademik başarı puanını oluşturmak için Türk Dili-1 ve matematik-1 notlarını içeren bölüm, ikinci bölümde zaman yönetimi anketi yer almaktadır. Elde edilen veriler, SPSS 17.0 programı kullanılarak bilgisayar ortamına aktarılarak verilerin analizinde bu programdan yararlanılmıştır. Sonuç olarak; araştırmamızda zaman yönetimi davranışları ile akademik başarı puanları arasında anlamlı pozitif ilişki bulunmuştur. Ayrıca akademik başarı notu yüksek olan grupların zaman yönetimi puanları da yüksek bulunmuştur.

Nowadays, time management has become more and more important due to the rapid change of technology. Hence, people have to plan their days efficiently to avoid daily hassles. Especially time management has become vital for college students to get good grades in their lectures. So, students must learn how to manage their time and how to improve their time management skills for having well education and business life. We researched students’ time management behaviours according to their various variables such as: gender, department, and so on… To achieve this goal, we used common survey as mentioned in literature. Therefore, the relationship between students' time management skills and academic success were examined. The structure of survey and the types of questions will describe below. The universe of research studies is consisted of Marmara University Vocational School of Technical Sciences students. The results reflect the properties of this universe. Wider sample of the research supplies more correct results. These research is a descriptive study. The universe of the survey consists of Marmara University Vocational School of Technical Sciences Computer Programming, Electronic Communications Technology, Electronics Technology, Electrical, Mechanical, Textile Technology, Biomedical Equipment Technology program students who first or second year in Marmara University. This survey is applied according to Britton and Tesser’s (1991) survey. Their survey adapted by Alay and Koçak (2002) which called "Time Management Survey". Time Management Survey consists of two main parts. The first part includes students' demographic characteristics and academic achievements scores. Turkish Language and math courses they take into consideration for calculating the academic success score. The other part of the survey includes time management and students spend time questions. Time Management Survey comprises three main factors and 27 questions. 16 of those questions are about “Time Planning”, 7 of those are about “Time Attitudes”, and 4 of those are about “Spending Time”. Likert-type scale is used in “Time Management Survey”. Survey data were transferred to SPSS 17.0; Then data analysed and comparison. The first part of the survey, 56% of them are girls, 44% of them are boys, 75.8% of them are 2nd year students, 61% of them are formal education students; and virtually all students are graduated from vocational lycee (90.5%). Survey reliability coefficient (Cronbach alpha) was found 0.675. The causes of time loss for students were followed in many ways. The main cause of time loss is “computer usage” (33%) the others are “internet usage” (24%), transport and traffic (13%), TV-radio (9%), sleep disorder (8%), routine work (7%), respectively. Talking with friends were found unnecessary due to the increasing of instant-message program usage. For determining the time management behaviours of students, their scores’ arithmetic mean were calculated and statistical analysis were made according to this average. Likert scale was used for the survey, so the midpoint is 3. Probable scores could be between “27” and “135” although the results were found between “43” and “135” and average score was found “3.07”. The relationship between “Time Management scores of students” and “academic success of students” was determined by using the Pearson Product Moment Correlation Coefficient method. Significant relationship between “attitudes time” and “academic achievement” was found r =-. 15, p <.01. Similarly, significant relationship between “attitudes time” and “time spend” was found r =. 405, p <.01. The significant relationship between “General Time Management” and “Academic Success” was found insignificant. Similarly, the significant relationship between “General Time Management” and “Time Planning” was found insignificant. According to this data, to increase academic success, time planning and avoiding time-consuming is important. The findings of research have shown that there is a positive relationship between students' academic achievement and time management skills. This relationship in terms of gender variable is in favour of female students. Recently, computers and internet are the most important emerging technologies that are used in every area of our lives. Especially in recent decade, internet usage has increased significantly, so internet using has become almost compulsory. People cannot imagine a life without the internet and computer. Internet usage has increased day by day and thanks to that all kinds of information are easily reachable. Because of the increased computer and internet usage, people have forgotten the importance of social life and become addicted to the internet (Karaman, K. ve Kurtoğlu, M. 2009). Especially students spend their time with using computers, internet and so forth more than average people. As a result of the fact that, they haven’t talked faceto- face and have become unsociable as they were. The relationship between academic success and time management skills of university students has shown that good time usage related with their academic achievement (Britton & Tesser, 1991; Mace & Tira, 1999; Nelson & Nelson, 2003). The findings of this research are parallel with above-mentioned research findings. General time management and sub-dimensions of time-holders for students were found significantly different according to gender. This difference in time-planning and time-consuming causes a case in favour of male students. Girl students use time management better than boys in Macan’s and others’ (1990) and Nelson’s (2003) articles. The findings of this study are parallel with above findings. The relationship between “Time management behaviours” and “achievement scores of course” was found significant. If academic success scores of the groups is high, time management scores are also high. In addition, significant positive relationship was found between “time management behaviours” and “achievement scores”. Hence, efficient time consuming could affect the students’ achievement scores of course, positively. In this study, students' time management behaviours researched thanks to the authors’ survey. As a result, to better determine students’ behaviours and its effects on the achievement scores, new studies can be done with valid and reliable scales and large samples. Finally, this research differs from the others in samples and universe, thus this research is one of the first studies in vocational high school of technical science. As far as the Marmara University considered, this study is the first research in vocational high school of technical science.
The relationship between vocational school student's academic success and time management